Pharmacology in Health Foods: Improvement of Vascular Endothelial Function by French Maritime Pine Bark Extract (Flavangenol) - Mamoru Ohkita; Yoshinobu Kiso; Yasuo Matsumura (Journal of Pharmacological Sciences, 2011)
Flavangenol is the French maritime pine bark extract (PBE). It consists of a concentrate of pine bark constituents such as catechin, taxifolin, and proanthocyanidins. Recent studies have shown that PBE has a strong antioxidant effect and exerts ameliorative effects on cardiovascular, skin, cognitive, and menstrual disorders, as well as in the context of other diseases and disease processes such as diabetes and inflammation. We have also obtained evidence that Flavangenol suppresses nuclear factor-kappa B (NF-κB) activation and the subsequent various NF-κB–induced gene expressions such as those of adhesion molecules and endothelin-1 in cultured vascular endothelial cells and that the antihypertensive effect of Flavangenol on deoxycorticosterone acetate–salt hypertensive rats is attributable to both its antioxidative property–related protective effects against endothelial dysfunction and the endothelium-dependent vasorelaxant effect, which is mediated by endothelial nitric oxide synthase activation. Furthermore, Flavangenol showed a renoprotective effect on ischemia/reperfusion-induced acute kidney injury in rats. These findings suggest that Flavangenol supplementation may be a promising candidate for the improvement of endothelial dysfunction and the prophylactic treatment of vascular diseases. Keywords:: Flavangenol, hypertension, ischemia acute kidney injury, nitric oxide synthase, antioxidative effect, health food